Bladder cancer therapy using a conformationally fluid tumoricidal peptide complex - Brisuda, Antonín; Ho, James C S; Kandiyal, Pancham S; Ng, Justin T-Y; Ambite, Ines; Butler, Daniel S C; Háček, Jaromir; Wan, Murphy Lam Yim; Tran, Thi Hien; Nadeem, Aftab; Tran, Tuan Hiep; Hastings, Anna; et al. (Nature communications, 2021)
Partially unfolded alpha-lactalbumin forms the oleic acid complex HAMLET, with potent tumoricidal activity. Here we define a peptide-based molecular approach for targeting and killing tumor cells, and evidence of its clinical potential (ClinicalTrials.gov NCT03560479). A 39-residue alpha-helical peptide from alpha-lactalbumin is shown to gain lethality for tumor cells by forming oleic acid complexes (alpha1-oleate). Nuclear magnetic resonance measurements and computational simulations reveal a lipid core surrounded by conformationally fluid, alpha-helical peptide motifs. In a single center, placebo controlled, double blinded Phase I/II interventional clinical trial of non-muscle invasive bladder cancer, all primary end points of safety and efficacy of alpha1-oleate treatment are reached, as evaluated in an interim analysis. Intra-vesical instillations of alpha1-oleate triggers massive shedding of tumor cells and the tumor size is reduced but no drug-related side effects are detected (primary endpoints). Shed cells contain alpha1-oleate, treated tumors show evidence of apoptosis and the expression of cancer-related genes is inhibited (secondary endpoints). The results are especially encouraging for bladder cancer, where therapeutic failures and high recurrence rates create a great, unmet medical need.
Keywords: regulace genové exprese u nádorů; Humans; Placebos; Oleic Acids; kyseliny olejové; sekvence aminokyselin; termodynamika; Protein Conformation; lidé; Endocytosis; peptidy; endocytóza; apoptóza; Peptides; stanovení cílového parametru; placebo; Amino Acid Sequence; Thermodynamics; protonová magnetická rezonanční spektroskopie; nádory močového měchýře; nádorové buněčné linie; Cell Line, Tumor; Proton Magnetic Resonance Spectroscopy; Gene Expression Regulation, Neoplastic; Urinary Bladder Neoplasms; Endpoint Determination; Apoptosis; konformace proteinů